Measuring English Grammar Test: A Rasch Analysis Approach - Fatimah, Ali; Noor Raha, Mohd Radzuan; Nor Suhardiliana, Sahar; Zuraina, Ali; Afifuddin Husairi, Hussain (Future Academy, 2017)
Students’ mastery of English language has always been the concern of many stakeholders especially the employers. Various standard language tests are used to measure the level of spoken and written language competency in general. However, not many language tests assess grammatical competency among the ESL learners. The grammar test which was developed aims to identify the students’ strengths and weaknesses in all 7 important grammatical elements such as Part of Speech, Tenses, Subject verb agreement, Relative Clauses, Conditionals, Passive and Verb Forms. The purpose of this study was to measure the reliability and validity of the instrument (UMP-EPT Grammar) using RASCH. The instrument which consists of 60 items was administered to 1694 first-year engineering students at Universiti Malaysia Pahang, Malaysia. Data collected were analyzed using WINSTEPS version 3.80.1. Findings revealed that item reliability and item separation was 1.0 and 20.53 respectively, while for person reliability and person separation, the results were .80 and 2.03 respectively. The study implies that the grammar test developed has great potential to be used for any high-stake test.